Marinobacter halodurans sp. nov., a halophilic bacterium isolated from sediment of a salt flat. Issue 12 (20th December 2020) - Yoo, Yeonjae; Lee, Hanbyul; Kwon, Bong-Oh; Khim, Jong Seong; Baek, Seungwoo; Pathiraja, Duleepa; Park, Byeonghyeok; Choi, In-Geol; Kim, Gyu-Hyeok; Kim, Beom Seok; Kim, Jae-Jin
Abstract : A Gram-staining-negative, aerobic, cream-coloured, marine bacterium, with rod-shaped cells, designated strain YJ-S3-2 T, was isolated from salt flat sediment of Yongyu-do, Republic of Korea. YJ-S3-2 T grew at pH 5.0–9.0 (optimum pH 7.0), 4–45 °C (optimum 30 °C) and with 1–18 % (w/v) NaCl (optimum 6 %). The results of 16S rRNA gene sequence analysis indicated that YJ-S3-2 T was closely related to Marinobacter segnicrescens SS011B1-4 T (97.0 %) followed by, ' Marinobacter nanhaiticus ' D15-8W (96.7 %), Marinobacter bryozoorum 50-11 T (96.7 %), Marinobacter koreensis DSMZ 179240 T T (96.5 %) and Marinobacter bohaiensis T17 T (96.5 %). The average nucleotide identity (ANI) and the genome to genome distance calculator (GGDC) estimate values between YJ-S3-2 T and related type strains were 73.7–79.8 and 19.9–22.5 %, and also 73.5 and 20.7 % with Marinobacter hydrocarbonoclasticus . YJ-S3-2 T was characterized as having Q-9 as the predominant respiratory quinone and the principal fatty acids (>10 %) were C16 : 0 (22.3 %), summed feature 9 (C17 : 1 iso ω9 c /C16 : 0 10-methyl, 13.8 %) and 3 (C16 : 1 ω7 c/ C16 : 1 ω6 c, 11.9 %). The polar lipids consisted of diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, two unidentified aminolipids and two unidentified phospholipids. The DNA G+C content of YJ-S3-2 T is 60.9 mol%. On the basis of the polyphasic taxonomic evidence presented in this study, YJ-S3-2 T should be classified as representing a novel species within the genus Marinobacter, for which name Marinobacter halodurans sp. nov. is proposed, with the type strain YJ-S3-2 T (=KACC 19883 T =KCTC 62937 T =JCM 33109 T ).